The relationship between electromagnetic radiation of mobile phones and male infertility – a review of the literature - Patrycja Maj; Natalia Sergiel; Agata Kania; Malwina Gonet; Karolina Miszczyk; Karolina Włodarczyk-Cybulska; Piotr Mozer; Jakub Maternia; Aleksandra Serwik-Trandasir; Michał Lazar (Journal of Education, Health and Sport, 2023)
Introduction: In recent years, there have been more and more concerns about whether wearing mobile phones near the reproductive organs, including the testicles, may cause significant health consequences, such as sperm dysfunction, decreased semen production, impaired testicular morphology, and thus become the cause of male infertility. Determining the relationship between the electromagnetic radiation of mobile phones and infertility in men may in the future reduce the male factor in the problem of infertility of couples and thus improve the quality of life.